Evaluación técnico-financiera de la obtención de aceite de semillas de guanabana (Annona muricata) (2020)
The objective of this work is to carry out the financial technical analysis to obtain oil from the soursop seed (Annona muricata). For this, the physical properties (particle size, density, aerated and packed bulk density, compressibility, porosity, form factor and angle of repose) and the proximal analysis of the seeds, later a factorial design of experiments was proposed in which the temperature and the drying time of the seeds during the thermal pretreatment were taken as independent variables, this pretreatment is an indispensable process for cold pressing extraction. From the yields obtained by the 4 treatments and their respective repetitions, it was concluded that the drying conditions with the highest oil yield compared to the others were at 50 °C for a period of 12 h. Based on these conditions, the conceptual design of the process at the pilot plant level was established and the costs associated with the acquisition and monthly operation of the selected equipments amount to $59.161.659 and $859.815 respectively.